Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00520-013-2016-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patient adherence to a complementary medicine treatment regimen in an integrative supportive care setting

Abstract: Previous use of CM for noncancer-related outcomes was found to be predictive of patient adherence to a CM treatment regimen provided within conventional oncology service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Initial IP consultations are followed by weekly or bi‐weekly CM treatment sessions over a 3‐ to 4‐month period, concluding with a second IP assessment in which ESAS and MYCaW questionnaires are re‐completed. Patients attending ≥5 consecutive integrative care sessions, with ≤30 days between sessions, are considered to be adherent to the integrative care process .…”
Section: Methodsmentioning
confidence: 99%
“…Initial IP consultations are followed by weekly or bi‐weekly CM treatment sessions over a 3‐ to 4‐month period, concluding with a second IP assessment in which ESAS and MYCaW questionnaires are re‐completed. Patients attending ≥5 consecutive integrative care sessions, with ≤30 days between sessions, are considered to be adherent to the integrative care process .…”
Section: Methodsmentioning
confidence: 99%
“…Among patients with chronic migraine, adherence to medications ranges from 26 to 29% at 6 months and decreased further to 17 to 20% at 12 months [ 32 ]. Studies have shown that about 66% of patients recommended for various CIM approaches followed through with appointment with their CIM provider [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment arm was subdivided into those with high adherence to the integrative care (AIC subgroup) program and those considered to be nonadherent (non-AIC subgroup). Adherence was defined as attending ≥4 CIM intervention sessions (not including the IP consultation), with ≤30 days between each treatment [18].…”
Section: Study Design and Settingmentioning
confidence: 99%